Self-starting mode-locked Tm-doped fiber laser using a hybrid structure of no core - graded index multimode fiber as the saturable absorber. (May 2019) - Li, Huanhuan; Wang, Zhaokun; Li, Can; Tian, Ying; Xiao, Zhen; Zhang, Junjie; Xu, Shiqing
Highlights: All-fiber nonlinear multimodal interference saturable absorber is used. It is a no core-graded-index multimode fiber cascaded saturable absorber. Output pulses with 1.25 ps at the wavelength of 1895 nm was obtained. Abstract: We experimentally demonstrated a passively mode-locked all-fiber Tm laser using a no-core-graded-index multimode fiber structure as a saturable absorber based on the nonlinear multimode interference. Stable fundamentally mode-locking operation was obtained at a pump threshold of 180 mW. The output soliton pulses had a centre wavelength, spectral width, pulse duration, and repetition rate of 1895.7 nm, 3.3 nm, 1.25 ps, and 18.91 MHz, respectively. This is a simple, low-cost, stable, and convenient laser oscillator, with many potential applications in eye-safe ultrafast photonics.